(untitled) - Gough, Alex (Oxford, 2007)
Veterinary practitioners and students are presented with many different and complex cases, and are expected to offer an accurate diagnosis quickly. The differential diagnosis list is one of the most important aspects of the problem-oriented approach to clinical diagnosis. Finding good lists in a readily available form can be difficult, and can involve laborious reference to multiple texts and sources. Differential Diagnosis in Small Animal Medicine brings this information together in one place in an easy reference format
Keywords: Diagnosis, Differential,Bệnh động vật,Animal Diseases; Handbooks,Chẩn đoán,Diagnosis